CV-QKD Security Limits Using Higher-Order Probabilistic Shaped Regular M-APSK Constellations - Almeida, Margarida; Pereira, Daniel; Muga, Nelson J.; Facão, Margarida; Pinto, Armando N.; Silva, Nuno A. (Anais do Workshop de Comunicação e Computação Quântica (WQuantum); 2022: Anais do II Workshop de Comunicação e Computação Quântica, 2022)
In this work we study the performance of M-symbol (M-)Amplitude and Phase Shift Keying (APSK) constellations for Continuous-Variable Quantum Key Distribution systems. Despite the gap still observed between the performance of higher order regular M-APSK constellations with binomial distribution for probabilistic shaping and the optimal performance of Gaussian Modulation, regular 128-APSK’s performance is better than irregular 256-APSK’s and almost the same as for regular 256-APSK. Moreover, higher-order regular M-APSK is secure for longer distances and higher values of mean number of photons per symbol, and is more resistant to excess noise.